Explorando a Diversidade de Pares de Caminhos Disjuntos por Arestas em Redes Ópticas Elásticas Sobreviventes - Girolimetto, Marina (2018)
In elastic optical networks, high bit rate can cause a major data loss problem when anetwork link or node failure occurs. To keep the network available and protected fromfailures, different protection schemes can be applied. In the dedicated path protectionscheme, working and backup paths are defined, which do not share resources, for each pairof nodes through algorithms that find disjoint paths. Generally, Suurballe and Tarjan’salgorithm is used to find shortest pairs of edge-disjoint paths such that the sum of thepath lengths is minimal. However, for the same pair of source and destination nodes, theremay be diverse shortest pairs of paths of the same minimum length, but with differentworking and backup paths lengths.In this work, two versions of the Suurballe and Tarjan’s algorithm are proposed to dealwith that diversity. For each pair of source and destination nodes of a given networktopology, these versions find the most balanced shortest pair of working and backup paths,with paths lengths with the smallest possible difference, and the least balanced, with pathslengths with the greatest possible difference. Both algorithms are tested and analyzed in aset of 40 2-edge-connected topologies of real-world optical telecommunication networks.The impact of these algorithms is investigated through the protection coefficient and thenumber of transponders required by dedicated-path protection schemes. Results show adifference of up to 29% in the working paths lengths between the strategies in the networkstested. Also, we evaluate the behavior of the algorithms in scenarios of dynamic traffic anddedicated path protection scheme, under simulations considering single link failures. Thus,it was identified from the studied networks that the blocking rate (performance metrics)of each algorithm will depend on the physical topology of the network.